PENERAPAN METODE COPY THE MASTER DALAM KEMAMPUAN MENULIS CERPEN SISWA KELAS XI SMK MULTI MEKANIK MASMUR PEKANBARU - Barus, Elvi Yana; Razak, Abdul; Elmustian, Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract:Copy The Master method is one method of many methods available. The aim of the researchers choosing the method is to enrich and succeed the ways of teaching students, especially in short storieswriting. In short story writing, the Copy The Master method were to imitate existing examples. Imitation can be done by adapting the background, adopting the theme, imitating the plot, borrowing the names of the characters, matching the conflict or taking the complete way of solving the story. Then the next process is the development of the story. The purpose of this study was to find out the application of the master copy method in the ability to write short stories of SMK Multi Mekanik Masmur Pekanbaru 11th Students. The research data was obtained through tests by measuring the level of ability to write short stories of SMK Multi Mekanik Masmur Pekanbaru 11th Students. The data analysis technique used in this study used the t test. The results of the t-test analysis of one sample in the experimental class testing were obtained significantly at -1,761> 12,515 <+1,761. This means that KKM 48 writing short stories is achieved. The results of the analysis show that the sig value is 0.521> 0.05 so it can be concluded that there is no difference in the posttest value of the experimental class between men and women. The results of the analysis found that there were differences in ability between short story writing skills before getting treated and getting the treatment of the Copy The Master method.Key Words: Copy the Master, Writing Skill